Invasive Treatment of Lower Limb Varicose Veins - Comparison of Treatment Methods - Ewa Piekarska; Krzysztof Dobrzeniecki; Remigiusz Luter (Journal of Education, Health and Sport)
Introduction and objective: Varicose veins in the lower extremities are a clinical manifestation of chronic venous disease. The condition is highly prevalent, with incidence increasing with age. Varicose veins are often accompanied by pain, and neglecting treatment can lead to complications such as superficial vein inflammation, deep vein thrombosis, and, most critically, pulmonary embolism. The primary aim of this study was to analyze and compare the efficacy and safety of available contemporary invasive methods for treating varicose veins in the lower extremities. Additionally, this paper addresses the epidemiology, etiology, and clinical presentation of chronic venous insufficiency.